Diversity of Types and Sizes of Lobster (Panulirus spp) Caught in the Waters of Lewoleba Bay, Lembata Regency, Nusa Tenggara Timur - Lasmi Lasmi (Jurnal Perikanan dan Kelautan, 2022)
This research was conducted in February-March 2021. The study was conducted in Nubatukan District, Lembata Regency. The purpose of this study was to determine the type and size of lobster caught by fishermen in the waters of Lewoleba Bay, Lembata Regency, East Nusa Tenggara. The methods used in collecting data are survey and interview methods. Based on the results of the study, researchers found two types of lobster caught by fishermen in the waters of Lewoleba Bay, namely: Bamboo Lobster (Panulirus versicolor) and Pearl Lobster (Panulirus ornatus). The size of lobster (Panulirus spp) caught by fishermen in the waters of Lewoleba Bay, has an average total carapace length of 20.79cm for the P.versicolor species and an average total length of 19.84cm for the P. ornatus species. Furthermore, the average weight of 1.96 kg for the type of P.versicolor and an average weight of 2.08 kg for the type of P. ornatus